Effects of the ACTH6-9-Pro-Gly-Pro peptide on the morphofunctional state of rat colon under conditions of chronic restraint stress - A. O. Vorvul; I. I. Bobyntsev; E. S. Mishina; O. A. Medvedeva; L. A. Andreeva; N. F. Myasoedov (Бюллетень сибирской медицины)
Aim. To study the morphofunctional state of the colonic wall in rats when using the N–terminal analog of the adrenocorticotropic hormone (ACTH) ACTH6-9-Pro-Gly-Pro (ACTH6-9-PGP) peptide under chronic stress.Materials and methods. The study was performed on 55 male Wistar rats, which were divided into 5 groups (n = 11): group 1 – control group (administration of saline solution without stress); group 2 – chronic restraint stress (CRS) + administration of saline solution; group 3 – CRS + administration of ACTH6-9-PGP at a dose of 5 μg / kg; group 4 – administration of ACTH6-9-PGP at a dose of 50 μg / kg; group 5 – administration of ACTH6-9- PGP at a dose of 500 μg / kg. A histologic examination of the rat colon was performed. The histologic architecture of the colonic wall, the depth of crypts, and the number of goblet cells were assessed. Furthermore, the number of granulocytes, plasma cells, lymphocytes, macrophages, and mast cells was counted.Results. The study demonstrated that chronic (14 days) restraint stress resulted in the development of inflammations in the colonic wall of the animals. Intraperitoneal administration of ACTH6-9-PGP at doses of 50 and 500 μg / kg daily throughout the entire time of stress exposure prevented the development of stress-induced alterations observed in the control animals. At the same time, anti-inflammatory effects of the peptide in the colonic wall and a decrease in the level of corticosterone in the blood serum were noted.Conclusion. The results of this work and data from other studies on the effects of N-terminal analogs of ACTH indicate the need for studying the mechanisms of their effect on inflammation and searching for targets of ACTH6-9-PGP.